Evaluación técnico financiera a nivel de laboratorio del diseño de lechadas de cementación, usando grano de caucho reciclado como material de control de pérdida (2018)
The present research project proposed the implementation of recycled rubber grain (GCR) in cement slurries for oil wells, the main purpose of this research was to enhance the control of loss circulation in cementing slurries. Using the recycled rubber grain as an additive in order to replace the control loss additives used by Superior Energy Services, in the oil well cementation that takes place in Castilla Field, focused in the superior and intermediate sections. To carry out the cement slurries tests, was necessary to have knowledge of the Castilla Field overview, the field’s lithology, the geology that delimitate the presence of hydrocarbons in the area, it was necessary to describe the overview for well cementing, its main operations, the cement used in oil & gas industry, the properties that define a cement slurry and the materials added to modify the slurry properties, also a description of the recycled rubber grain (GCR), it’s industrial overview and properties was developed.